Enhancing the production of recombinant acidic α-amylase and phytase in Pichia pastoris under dual promoters [constitutive (GAP) and inducible (AOX)] in mixed fed batch high cell density cultivation. Issue 10 (October 2016) - Parashar, Deepak; Satyanarayana, T.
Graphical abstract: Highlights: Strategy has been developed to express proteins under dual promoters ( AOX and GAP ). Dual promoters led to improvement in productivity of α-amylase and phytase. The presence of multiple copies of Amy and Phy did not affect growth of P. pastoris . Abstract: The methylotrophic yeast Pichia pastoris is widely used as an expression host for heterologous protein production using methanol as a sole carbon source. Slow growth rate and low specific productivity in methanol are, however, bottlenecks for its utility at industrial scale production. We have, therefore, developed a strategy for overcoming the bottlenecks and improving production of heterologous proteins. Four recombinant P. pastoris strains (Amy-AOX and Phy-AOX that produce α-amylase and phytase under only AOX promoter, and Amy-GAP-AOX and Phy-GAP-AOX that produce α-amylase and phytase under both AOX and GAP promoters) were generated. This has led to 1.8- and 1.3-fold improvement in α-amylase and phytase production in mixed fed batch cultivation as compared to that of Amy-AOX and Phy-AOX. The recombinant strains Phy-GAP-AOX integrated five copies of Phy (3 copies under AOX promoter and two copies under GAP promoter), while Phy-AOX integrated 3 copies of Phy under AOX promoter. On the other hand Amy-GAP-AOX integrated a total of 3 copies of Amy (one copy under AOX promoter and two copies under GAP promoter), while Amy-AOX integrated one copy under AOX promoter. The data suggest that this strategy would be useful in producing high titres of other heterologous proteins too in P. pastoris .